2015
DOI: 10.1016/j.bjorl.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nasal shape after orthognathic surgery

Abstract: Surgeries of maxillary advancement and superior reposition tend to cause elevation and advancement of the nasal tip, as well as enlargement of the nasal base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 13 publications
0
27
0
4
Order By: Relevance
“…These procedures objectively mobilize the nose three-dimensionally; Dantas et al (2015) reported that surgery for anterior and superior maxillary repositioning produces movements of the nasal tip upward in 85% of the cases, advancement of the tip in 80%, rotation of the tip in 80% and widening of the nasal base in 95%, causing significant cosmetic changes in this area.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures objectively mobilize the nose three-dimensionally; Dantas et al (2015) reported that surgery for anterior and superior maxillary repositioning produces movements of the nasal tip upward in 85% of the cases, advancement of the tip in 80%, rotation of the tip in 80% and widening of the nasal base in 95%, causing significant cosmetic changes in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Widening of the alar base occurs following almost all maxillary osteotomies, especially with impaction and/or advancement( 6 ) or segmental advancement and widening ( 7 ).It is the most consistently reported change in the literature ( 6 , 7 , 8 , 9 , 10 ). It has also been noted to occur with surgically assisted maxillary expansion ( 7 , 11 , 12 ).…”
Section: Effects Of Maxillary Orthognathic Surgery On Nasal Morphologmentioning
confidence: 99%
“…Other nasal changes also occur with maxillary surgery and generally thought to be dependent on the direction and magnitude of the maxillary move. Maxillary advancement and superior repositioning tends to cause elevation and advancement of the nasal tip, as well as enlargement of the nasal base ( 6 , 8 ). Rotation of the tip, exaggeration of the supratip break and softening of the dorsal hump may follow maxillary advancements ( 6 ).…”
Section: Effects Of Maxillary Orthognathic Surgery On Nasal Morphologmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequentemente, há uma mudança no arranjo facial, a qual influencia a aparência do nariz externo (77).…”
Section: Marcação Dos Pontos De Referência No Nariz Externounclassified